Evaluating the efficacy of mechanical removal of Listeria monocytogenes from stainless steel and ceramic surfaces. - Troetsch D., Erin M. (Zamorano: Escuela Agrícola Panamericana, 2025)
This study conducted at Louisiana State University's Animal and Food Science Laboratory, investigated the detachment and bio-transfer of Listeria monocytogenes on stainless steel and ceramic surfaces, simulating food and non-food contact surfaces. An independent samples t-test design with 3 repetitions and 4 replicates each was used, employing mechanical action with glass beads to detach biofilms. After treatment, bacterial growth and transfer to fresh milk were assessed, simulating real-world contamination scenarios. The Listeria monocytogenes V7 strain (milk-associated outbreak strain) was used to form biofilms on sterilized stainless steel and ceramic tiles. Mechanical action with glass beads in phosphate-buffered saline (PBS) and vortexing for two minutes each detached bacteria, followed by serial dilutions and plating for analysis. Results indicated significantly higher biofilm detachment from stainless steel due to its lower porosity compared to ceramic. Mechanical force effectively reduced biofilm attachment, with bacterial transfer being lower within the first two minutes but significantly increasing by five minutes due to longer exposure. This study emphasizes the importance of stringent cleaning protocols, combining mechanical action with disinfection to ensure pathogen removal, particularly on stainless steel. Minimizing contact time between surfaces and fresh foods is crucial for reducing cross-contamination risks, ensuring food safety, and maintaining hygiene standards in the dairy industry, particularly in preventing biofilm formation and bacterial spread.